Opportunities and Challenges to Implementing Genomic Selection in Clonally Propagated Crops - Gemenet, D.; Khan, A. (Springer, 2017)
Clonal propagation of fruits, flowers, and forest trees leads to high levels of heterozygosity, fixes favorable combinations of traits, eliminates undesirable deleterious effects, allows easy identification, propagation of favorable mutations, and is an efficient method for in vitro and ex vitro maintenance and conservation. However, these same characteristics pose challenges to genetic improvement. Many clonal fruits and forest trees have a long juvenile phase, extensive outcrossing, widespread hybridization, limited population structure, multiple origins, and ongoing crop–wild gene flow, and have suffered from domestication bottlenecks, and are polyploid. Breeding clonal crops requires a crossing step involving two heterozygous parents, as a break to create genetic variation that can be exploited during selection in subsequent cycles, before reverting to clonal selection. The presence of several segregating alleles, overdominance and epistatic interactions, at each locus of highly heterozygous clonal crop decreases efficiency of phenotypic selection in breeding programs and genetic studies. Genomic selection (GS) that uses genome-wide genotypic data to predict the phenotypic performance of a genotype by estimating its breeding value has the potential to increase efficiency of clonal crop breeding. In this chapter, potential use and challenges of GS to expedite the breeding process in clonally propagated crops are discussed, with examples. We identify challenges associated with specific features of clonal crops to be addressed in GS models and highlight development of improved marker and bioinformatics platforms to distinguish between paralogous copies and to incorporate partial heterozygosity and allele dosage determination.